Analysis Interaction of Nicotinamide and Ascorbic Acid and Its Derivatives as Active Substances in Skin Lightening Cosmetic Products - Hidayati, Pratiwi Al Fitri; Auli, Winni Nur; Aziz, Syaikhul; Zaqia, Lulu; Liswatini, Putri (Journal of Science and Applicative Technology, 2025)
Ascorbic acid and its derivatives with nicotinamide are often used as skin lightening, anti-aging, and anti-pigmentation agents. Combining these two active substances may increase the risk of instability due to degradation. This research was conducted to determine the effect of nicotinamide concentration on the degradation process of ascorbic acid and its derivatives, and to determine the degradation products formed using liquid chromatography-mass spectrometry (LC-MS). The study was conducted by combining nicotinamide concentrations ranging from 5 to 15 micrograms per milliliter with incubation times of 1, 2, 3, and 24 hours to react with ascorbic acid and its derivatives. The spectral shape and maximum wavelength were analyzed using a UV-Vis spectrophotometer. Samples that showed changes in chemical structure were subsequently analyzed by LC-MS to identify degradation products. The results showed that only the combination of ascorbic acid and nicotinamide shifted the maximum wavelength and generated a new peak at 310 nm after 24 hours of incubation. Nicotinamide can accelerate the degradation process of ascorbic acid. The LC-MS analysis results show that the degradation products formed from the combination of ascorbic acid and nicotinamide samples are dehydroascorbic acid and 3-hydroxy-2-pyrone. These findings highlight the importance of incorporating stabilizing agents into cosmetic formulations containing unstable active ingredients, such as ascorbic acid, to ensure product stability during storage and use.